Hulless Black Barley as a Carrier of Probiotics and a Supplement Rich in Phenolics Targeting Against H2O2-Induced Oxidative Injuries in Human Hepatocarcinoma Cells - Wu, Han; Liu, Hao-Nan; Liu, Chun-Quan; Zhou, Jian-Zhong; Liu, Xiao-Li; Zhang, Hong-Zhi (Frontiers in Nutrition, 2022)
Lactic acid bacteria can provide benefits for human beings and transform phenolic substances to improve their potential functionality. It was of interest to develop black barley as a carrier of probiotics and nutraceutical supplement rich in more antioxidants. Due to fermentation, bacterial counting and free phenolic content in black barley increased to 9.54 ± 0.22 log cfu/mL and 5.61 ± 0.02 mg GAE/mL, respectively. Eleven phenolic compounds, including nine isoflavones and two nitrogenous compounds were characterized using UPLC-QTOF-MS, among which epicatechin, hordatine and pelargonidin aglycone were largely enriched. Moreover, free phenolic extracts from fermented barley (F-BPE) played a greater role in scavenging DPPH radicals, reducing Fe3+ to Fe2+, and increasing oxygen radical absorbance capacity (1.94-, 1.71-, and 1.35-fold at maximum for F-BPE vs. UF-BPE, respectively), compared with those from un-fermented barley (UF-BPE). In hepatocarcinoma cells, F-BPE also better inhibited ROS production and improved cell viability, cell membrane integrity, SOD activity, and nonenzymatic antioxidant GSH redox status (2.85-, 3.28-, 2.05-, 6.42-, and 3.99-fold at maximum for F-BPE vs. UF-BPE, respectively).